Relação conceitual entre ergonomia e qualidade de vida no trabalho: a humanização do trabalho sob a ótica da análise ergonômica - Prachum, Carla Leal (2023)
Work occupies an extremely important space in people's lives, it is a form of expression and satisfaction and represents the efforts and abilities developed throughout life. This research sought to understand how ergonomic practices have developed, identifying the motivation for the implementation of ergonomic practices, the ergonomic practices carried out and the strategies adopted for their implementation, and their perceptions. Given the above, the research question of this project is adopted to know what are the characteristics of quality of life at work that can be enhanced by adopting ergonomic measures arising from the execution of ergonomic work analysis. By conducting bibliographical research on ergonomics and ergonomic analysis of work, as well as on quality of life at work, this study proposes to present a systematic review of the literature conceptually relating ergonomics and quality of life at work, making it possible to verify the several applications that ergonomics has allied to quality of Life, involving physical, psychological and organizational aspects that directly impact the health and safety of workers. It is concluded that in the reviewed studies, the ergonomics research provided the improvement of performance, organization and, consequently, the quality of Life. Thus, we sought to demonstrate the relevance of the study carried out to highlight the importance of the topics covered and how they could influence the life of human beings and their well-being.